Reduction of aggression evoked by sounds using noncontingent reinforcement and time‐out. Issue 3 (29th June 2015) - Dupuis, Danielle L.; Lerman, Dorothea C.; Tsami, Loukia; Shireman, Molly L.
<x xml:space="preserve">Abstract</x> Some individuals with developmental disabilities engage in problem behavior to escape or avoid auditory stimuli. In this study, a 6‐year‐old boy with autism engaged in severe aggression in the presence of specific sounds. Following an assessment based on the procedures described by McCord, Iwata, Galensky, Ellingson, and Thomson (2001), we treated negatively reinforced behavior using noncontingent reinforcement and time‐out from positive reinforcement in the absence of extinction. Treatment was effective in reducing aggression across multiple sounds.